2021
DOI: 10.48550/arxiv.2110.11138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The emergence of gapless quantum spin liquid from deconfined quantum critical point

Wen-Yuan Liu,
Juraj Hasik,
Shou-Shu Gong
et al.

Abstract: A quantum spin liquid (QSL) is a novel phase of matter with long-range many-body quantum entanglement where localized spins are highly correlated with the vanishing of magnetic order. Such exotic quantum states typically host emergent gauge fields and fractional excitations. Here we show that a gapless QSL can naturally emerge from a deconfined quantum critical point (DQCP), which is originally proposed to describe Landau forbidden continuous phase transition between antiferromagnetic (AFM) and valence-bond so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…The resulting Fermi surfaces, shown in Fig. 7(a), are similar to that obtained for Bi2201: upon hybridization, the two large Fermi surfaces (red lines) split by the bilayer coupling, transform into gapless Z 2 spin liquid which has attracted significant recent interest [32][33][34][35][36][37][38][39][40][41][42][43][44][45], but the paramagnon fractionalization approach allows for a very wide range of possibilities on the second hidden layer.…”
Section: Bi2212supporting
confidence: 54%
See 3 more Smart Citations
“…The resulting Fermi surfaces, shown in Fig. 7(a), are similar to that obtained for Bi2201: upon hybridization, the two large Fermi surfaces (red lines) split by the bilayer coupling, transform into gapless Z 2 spin liquid which has attracted significant recent interest [32][33][34][35][36][37][38][39][40][41][42][43][44][45], but the paramagnon fractionalization approach allows for a very wide range of possibilities on the second hidden layer.…”
Section: Bi2212supporting
confidence: 54%
“…One promising description of the spinons in the second hidden layer in a model without disorder is the gapless Z 2 spin liquid, which has received significant attention recently [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Appendix A presented results for the electronic self energy using this gapless Z 2 spin liquid, and showed that this liquid can yield significant damping of the fermions at the pseudogap energy in the antinodal region, and also improve correspondence with observations.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Numerical evidence has since accumulated for the presence of a VBS phase in the J 1 -J 2 modelin particular, it was recently shown that a non-zero antiferromagnetic third-nearest-neighbor interaction J 3 stabilizes a clear VBS phase in a large parameter range of J 2 /J 1 [15], and this phase is argued to be stable down to J 3 = 0. The nature of the Néel-VBS transition in this model has remained a question of significant debate.…”
Section: Introductionmentioning
confidence: 99%